Antibacterial Effect of Aqueous and Ethanol Extracts of Moringa oleifera Leaves on Methicillin Resistant Staphylococcus aureus (MRSA) Isolates obtained from a University Community: Antibacterial Effect of Moringa oleifera leaves on MRSA - Iwetan, Benedict Bolakponumigha; Okwu, Maureen Uchechukwu; Enwa, Felix Oghenemaro (International Pharmacy Acta, 2023)
Antibacterial Effect of Aqueous and Ethanol Extracts of Moringa oleifera Leaves on Methicillin Resistant Staphylococcus aureus (MRSA) Isolates obtained from sampled in a University Community. Methicillin Resistant Staphylococcus aureus (MRSA) are strains of the Staphylococcus aureus that are resistant to the action of methicillin and related beta-lactam antibiotics. MRSA infections have now become a major public health concern and its prevalence is also increasing globally. This study focused on the prevalence of MRSA obtained from clinical samples. The failed antibacterial agent conventional used for treatment necessitated the investigation of Antibacterial Effect of Aqueous and Ethanol Extracts of Moringa oleifera Leaves on Methicillin Resistant Staphylococcus aureus (MRSA) Isolates. A total of 296 samples were collected from Armpit, Ear, High Vaginal, Mouth, Nose swabs, Urine and Semen, from which 143 (48.3%) isolates of S. aureus were obtained. The MRSA prevalence 105(35.5%). There were no association (no significant difference P>0.05) in the prevalence of S. aureus and MRSA with regards to Age distribution, Sex and Sample types. A Total of 35 selected isolates of MRSA were analyzed for their antibiotic susceptibility and effect of Aqueous and Ethanol Extracts of Moringa oleifera Leaves. They were highly susceptibility to Ciprofloxacin 26(74.3%), Gentamicin 31(88.6%), Streptomycin 32(91.4%) and Levofloxacin 32(91.4%). However, low levels of MRSA susceptibility were recorded for Vancomycin 21(60%) and Ampiclox 31(88.6%). Multidrug resistant (isolates resistant to drug agents ≥ 4) recorded is 9(25.7%) of the 35 isolates studied. Comparing the anti-MRSA property of Moringa oleifera leave extracts between aqueous at ≤ 12.5 mg/mL and 70% ethanol extracts at 25 mg/mL on 35 selected MRSA isolates using Mann Whitney test their Mean ± SD zones of minimal inhibition are (1.86 ± 5.91 mm) and (0.54 ± 2.16 mm) respectively. Statistically at P˂0.0.5 the null hypothesis was rejected P= 0.047. Meaning aqueous extract mean zones of inhibition is higher than that of 70% ethanol extracts. Therefore, aqueous extraction of M. oleifera leaves should be studied intensively as a potential source for drug development for the treatment of MRSA infections.